2002
DOI: 10.1063/1.1521584
|View full text |Cite
|
Sign up to set email alerts
|

Interaction corrections to transport due to quasibound states in open quantum dots

Abstract: We formulate a many-body model of transport in open quantum dots, which is based upon the idea of an enhanced electron-electron interaction in the vicinity of a quasibound state. Our studies suggest that the effect of including this peaked interaction is to increase the amplitude of the conductance fluctuations, beyond the value expected from a single-particle treatment. While the role of interactions in transport through open dots has attracted little theoretical attention, our results demonstrate the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, for most applications it is sufficient to consider a vector w that maximizes the entropy at an effective temperature T * (T, V G , V D ) under the (weaker) subsidiary condition that ρMB [w] = ρ within the relevant subspace, where ρMB [w] denotes the many-body result. 19,28,29 (Under moderate bias conditions, it is justified to assume T * ≈ T . )…”
Section: Multi-configurational Self-consistent Green's Functionmentioning
confidence: 99%
“…However, for most applications it is sufficient to consider a vector w that maximizes the entropy at an effective temperature T * (T, V G , V D ) under the (weaker) subsidiary condition that ρMB [w] = ρ within the relevant subspace, where ρMB [w] denotes the many-body result. 19,28,29 (Under moderate bias conditions, it is justified to assume T * ≈ T . )…”
Section: Multi-configurational Self-consistent Green's Functionmentioning
confidence: 99%
“…It is clear from these figures that our simulations are successful in reproducing the main features of experiment. The discrepancy between the value of T * , and the cryostat temperature of 0.01 K, cannot be attributed to an inability to cool the electrons in the dot below 0.3 K. Later on in this review, we will discuss the observation of temperature-dependent resistance variations in these dots, which exhibit a consistent change at temperatures well below 0.05 K [38][39][40]. Another contribution to T * is from decoherence-induced broadening of the dot levels, and the magnitude of this effect is determined by the value of the phase-breaking time (τ φ ).…”
Section: Experimental Signatures Of the Open-dot Spectrummentioning
confidence: 99%
“…Based on studies of the temperature-dependent behaviour in several different devices, we have suggested that the initial increase of the dot resistance with decreasing temperature is The dashed lines are fits to the form of equation ( 10) while the dotted line area fits to equation (10) with an additional log term added. Figure adapted with permission from [40]. Copyright, American Institute of Physics (2002).…”
Section: Temperature-dependent Transport and The Signatures Of Intera...mentioning
confidence: 99%
“…Quantitative expressions for the temperature dependence of interaction-introduced conductance fluctuations have been derived. A detailed comparison of experimental results with the predictions obtained from the peakedinteraction model can be found in [32].…”
Section: Discussionmentioning
confidence: 99%